First Resource Indexes: Trends, Approaches, and Prospects for Russia - Anna E. Tsymbalova; Vladimir V. Sikirazh (СибСкрипт)
The article traces the development of indexes in the socio-economic and political spheres since 1995, i.e., Human Development Index, Index of Economic Freedom, Democracy Index, and Doing Business Index. The indexes are means of soft power that shape the image of states by determining their resourcefulness. The authors focused on the earliest foreign resource potential ratings, their transformation over time, and relevance for Russian policy. The methods of problem-historical approach, comparative analysis, synthesis, and qualitative content analysis revealed the level of political and economic freedom as the major idea behind the index system and the agencies that develop them. However, the commitment of these agencies to the dominant neoliberal paradigm makes them biased, manifesting itself both in the rating results and its criteria. The Western economic metrics seem to rely on the doubtful libertarian thesis about the correlation between democracy and economic well-being. Their methodology is inaccurate and unobjective, which leads to lobbying or data manipulation caused by affiliation or direct dependence on particular beneficiaries.